Eficiencia del pasto vetiver (Chrysopogon zizanioides) en la remoción de la carga contaminante de las aguas residuales de la industria de almidón - Segovia Zambrano, Angela Mariana (2021)
The objective of the following work was to evaluate the efficiency of vetiver grass (Chrysopogon zizanioides) in the removal of the pollutant load of wastewater from the starch industry, for this a completely random design with 4 treatments was used, each one With 3 repetitions, which were distributed 4, 12, 25 cuttings respectively in a volume of 18 liters of residual water, the treatment lasted 22 days in which the physical-chemical parameters were monitored. These wastewaters presented high concentrations of BOD5 (760 mg / L) thus denoting high amounts of organic matter, they also showed an acid characteristic with a pH value of 4.1; phosphorus presented high data of 20.47 mg / L and TSS 0.69 mg / l. In the adaptation of the plant to wastewater, he showed that vetiver can survive in hydroponic and submerged conditions for 3 months. In the case of BOD5, it had an efficiency that reached 70.75% removal in (A3), for the rest of the monitored parameters it was obtained in SST with 40.45%, phosphorus with 50.81%, and nitrogen with 59.54%, unlike the control that presented values well below the vetiver treatments, in the case of the pH it was very favorable since it went from 4.1 (acid) to 7.50 (neutral). The research had a total implementation value of $ 328.90 value that includes raw material, labor and indirect costs, these values vary according to the amount of vetiver used in each treatment.